(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The spleen is the most frequently injured organ in blunt abdominal trauma, and a missed splenic injury is the most common cause of preventable death in trauma patients. The purpose of this study was to investigate the prevalence of spleen injuries in non surviving patients with abdominal trauma by evaluating the compiled autopsy study data. Abbreviated Injury Scale is used to determine the severity of splenic injuries. In the present study, 18.8% of victims belong to third decade and 29.7% of victims belong to fourth decade. Women were less involved than men with a ratio of 1:3.5. In our study, the vast majority of patients, 54 (84%), sustained blunt injuries and the remaining, 10 (16%), patients had penetrating injuries. Since the spleen is highly vascular and friable having immense immunological and haematological importance, timely diagnosis and management of splenic injuries goes a long way in improving the mortality and morbidity rates in trauma cases.